(untitled) - Bejan, Adrian (Hoboken, 2006)
Adrian Bejan's Advanced Engineering Thermodynamics established itself as the definitive volume on this challenging subject. Now, his Third Edition builds on the success of its trailblazing predecessors by providing state-of-the-art coverage in a slimmer, more convenient book.
Nguyên lý các quá trình chế biến thực phẩm
Keywords: Thermodynamics